(untitled) (Tzintzun, Revista de Estudios Históricos, 2016)
This collaboration is an analysis of “The Defenders of National Integrity”, a mural painted by Alfredo Zalce in 1951 which was funded by the Michoacan Museum and the National Institute of Fine Arts. The mural, which many critics consider to be Zalce’s best, is located in the stairway of the Michoacan Regional Museum, and measures 135m². The objective of this study is not only from the perspective of its composition and theme but also from the trajectory of Zalce’s professionalism in the content of his works, of the ideas and pictorial influences he united, and of the influence of other Mexican muralists and other artists and writers affiliated with the Writer and Artist’s Revolutionary League (LEAR) and the Popular Graphics Workshop (TGP).